2003
DOI: 10.1021/ja027225p
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ene Reactions of Singlet Oxygen. A Two-Step No-Intermediate Mechanism

Abstract: The mechanism of the ene reaction of singlet ((1)delta(g)) oxygen with simple alkenes is investigated by a combination of experimental isotope effects and several levels of theoretical calculations. For the reaction of 2,4-dimethyl-3-isopropyl-2-pentene, the olefinic carbons exhibit small and nearly equal (13)C isotope effects of 1.005-1.007, while the reacting methyl groups exhibit (13)C isotope effects near unity. In a novel experiment, the (13)C composition of the product is analyzed to determine the intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
271
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(282 citation statements)
references
References 64 publications
8
271
0
3
Order By: Relevance
“…The reaction path is likely to involve a twostep no-intermediate mechanism as proposed by Singleton et al for reactions of singlet oxygen. [12] In transition structures 10 and 11, the fluorine substituent prefers to reside inside by 2.1 kcal mol À1 . …”
Section: In Memory Of Charles Mioskowskimentioning
confidence: 99%
“…The reaction path is likely to involve a twostep no-intermediate mechanism as proposed by Singleton et al for reactions of singlet oxygen. [12] In transition structures 10 and 11, the fluorine substituent prefers to reside inside by 2.1 kcal mol À1 . …”
Section: In Memory Of Charles Mioskowskimentioning
confidence: 99%
“…In the case of the pyrone derivative,c oordination of alkyne to III Pyr results in formation of IV Pyr having two energetically accessible fates. H-transfer through TS IVPyr-VPyr (+ 3kJmol À1 )r esults in the formation of alkynyl complex V Pyr which would liberate 6h, however insertion of the alkyne into the MnÀCbond of IV Pyr through TS IVPyr-VIPyr (+ 4kJmol À1 )affords more energetically favourable VI Pyr .T he process seen for reactions of 2h has resulted in the formation of two CÀCb onds.Preliminary investigations indicate that this proceeds through a"two-steps no intermediate" pathway [15] with the initial insertion into the Mn À Cb ond, followed by cyclization giving as ix-membered ring without an intermediate.However,inVI Pyr the Mn is h 3 -coordinated to the pendant pyridyl group and newly formed ring. To form 10 Pyr ,which is the lowest point on the potential energy surface at À320 kJ mol À1 ,t he Mn needs to migrate to the alternative ring-face.W ep ostulate that this involves migration onto one of the phenyl rings in the ligand, for example, VIIa Pyr .The ring rotates allowing the Mn to migrate to the other face of the pentadienyl system, giving VIIb Pyr .Itis reasonable to presume that this proceeds via al ow energy ring-walking process.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[42] A collaborative effort by the Singleton, Houk, and Foote groups used 13 C KIEs and quantum mechanical methods to show that this reaction takes place through a two-step-nointermediate mechanism. [3,43] CCSD(T) single-point energies computed on a grid of B3LYP structures revealed that the PES bifurcates after a common TS (26; Figure 4). The second sequential TS 27 is the elusive perepoxide-like structure with shorter partial C À O bond lengths and connects the two ene products.…”
Section: Ene Reactionsmentioning
confidence: 99%
“…[2] This type of potential energy surface describes a reaction mechanism that is different from stepwise or concerted and has been referred to as a two-step-no-intermediate mechanism. [3] When a reaction has this type of surface, the rate of selective formation of one product relative to another is governed by the potential energy surface shape and resulting dynamic effects. [4] Early reported examples of bifurcating reactions involved simple isomerizations, rearrangements, and addition reactions.…”
Section: Introductionmentioning
confidence: 99%